×
Language:

Assignment 5 — Solutions 2/13/04 (revised 2/23/04)
Problem 3.10
(a)We get to integrate our relations from last time. Joy.
H
f
,
z
L
=
:
,
-p
ê
2
<f<p
ê
2
-
,
p
ê
2
<f<
3
p
ê
2
A
0
n
=
1
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅp
L I
m
H
n
p
b
ê
L
L

‡
-p
ê
23
p
ê
2

f
‡
0
L

z
H
f
,
z
L

sin
J
n
p
z
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
L
N:
A
mn
B
mn
>
=
2
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅp
L I
m
H
n
p
b
ê
L
L

‡
-p
ê
23
p
ê
2

f
‡
0
L

z
H
f
,
z
L

:
cos
m
f
sin
m
f
>

sin

J
n
p
z
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
L
N
,
m
0The range of
f
integration has been shifted to be convenient for
(can be done since it's periodic). For
m
,
n
0:
:
A
mn
B
mn
>
=
2

ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅp
L I
m
H
n
p
b
ê
L
L

‡
0
L

z
sin
J
n
p
z
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
L
N

ikjjj‡
-p
ê
2
p
ê
2

f-
‡
p
ê
23
p
ê
2

f
y{zzz

:
cos
m
f
sin
m
f
>
=
2

ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅp
L I
m
H
n
p
b
ê
L
LB
-
L
ÅÅÅÅÅÅÅÅÅÅÅ
n
p
cos
J
n
p
z
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
L
NF
0
L

1
ÅÅÅÅÅÅÅ
m
ÄÇÅÅÅÅÅÅÅÅÅ:
sin
m
f-
cos
m
f
>
-p
ê
2
p
ê
2
-
:
sin
m
f-
cos
m
f
>
p
ê
23
p
ê
2
ÉÖÑÑÑÑÑÑÑÑÑ
=-
2

ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
nm
p
2

I
m
H
n
p
b
ê
L
L@H
-
1
L
n
-
1
D

:
2

sin
H
m
p
ê
2
L
-
sin
H
3

m
p
ê
2
L
+
sin
H
m
p
ê
2
L
0
+
cos
H
3

m
p
ê
2
L
-
cos
H
m
p
ê
2
L>
=
2

@
1
-
H
-
1
L
n
D
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
nm
p
2

I
m
H
n
p
b
ê
L
L

:
4sin
H
m
p
ê
2
L
0
>
A useful table from the CRC handbook of Standard Mathematical Tables and Formulae (30th edition):
n
œ
n
even
n
odd
n
ê
2odd
n
ê
2evensin
n
p
00000cos
n
p
H
-
1
L
n
+
1
-
1
+
1
+
1sin
n
p
ê
20
H
-
1
L
H
n
-
1
2
00cos
n
p
ê
2
H
-
1
L
n
ê
2
0
-
1
+
1from which we deduce that
A
mn
=
0 for even
m
and
A
mn
H
-
1
L
H
m
-
1
2
for odd
m
.
A
m
0
=
0
=
B
m
0
fromsin
H
n
p
z
ê
L
n
=
0
=
0 and
B
0
n
=
0 since sin
m
f
§
m
=
0
=
0. Also
A
0
n
=
0 because the
f
integral is over
H
f
,
z
L
onlywhich is odd in the given range. Since
A
mn
1
-
H
-
1
L
n
it vanishes for even
n
, and the factor is 2 for odd
n
.Finally:
A
mn
=
16

H
-
1
L
H
m
-
1
2
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
nm
p
2

I
m
H
n
p
b
ê
L
L
,
n
,
m
odd;all other coefficients vanish
1

F
H
v
,
f
,
z
L
=
16

ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅp
2

n
,
m
odd
H
-
1
L
H
m
-
1
2
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
nm
p
2

I
m
H
n
p
b
ê
L
L

cos
H
m
f
L

sin
J
n
p
z
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
L
N

I
J
n
pvÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
L
N
(b)For
b
ê
L
`
1, which means
v
ê
L
`
1 since
v§
b
, we have from the asymptotic expansion 3.102:
I
m
H
n
pv
ê
L
L
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
I
m
H
n
p
b
ê
L
L
º
H
n
pv
ê
2

L
L
m
êH
2

m
+
2
L
!ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
H
n
p
b
ê
2

L
L
m
êH
2

m
+
2
L
!º
J
vÅÅÅÅÅÅÅÅ
b
N
m
One might worry that the arguments to
I
m
are not strictly always small since
n
ranges to infinity, but in a com-pletely handwaving manner one may hope that the effects of increasing
n
in numerator and denominator magi-cally cancel out. For those of you who are rightly dubious you can probably go to the series expansion (Gradsh-teyn and Ryzhik 8.445):
I
n
H
z
L
=
=
0
1
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
! G
H
n+
+
1
L

J
z
ÅÅÅÅÅ
2
N
n+
2

(exact)and use the binomial theorem etc. to figure out the specifics. If you manage do please tell. Anyway at
z
=
L
ê
2and seeing from our table that sin

H
n
p
ê
2
n
odd
=
H
-
1
L
H
n
-
1
2
:
F
H
v
,
f
,
z
L
º
16

ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅp
2

n
,
m
odd
H
-
1
L
H
m
-
1
2
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
nm
p
2

H
-
1
L
H
n
-
1
2

cos
H
m
f
L

J
vÅÅÅÅÅÅÅÅ
b
N
m
=
16

ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅp
2

n
=
0
H
-
1
L
n
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
2

n
+
1

m
=
0
H
-
1
L
m
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
2

m
+
1

cos
@H
2

m
+
1
L
f
D

J
vÅÅÅÅÅÅÅÅ
b
N
2

m
+
1
=
16

ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅp
2
pÅÅÅÅÅÅ
4

m
=
0
H
-
1
L
m
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
2

m
+
1

1
ÅÅÅÅÅ
2

I
Â
H
2

m
+
1
L
f
+
H
2

m
+
1
L
f
M

J
vÅÅÅÅÅÅÅÅ
b
N
2

m
+
1
=
2

ÅÅÅÅÅÅÅÅÅÅÅÅp
m
=
0
H
-
1
L
m
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
2

m
+
1
BJ
Âf
vÅÅÅÅÅÅÅÅ
b
N
2

m
+
1
+
J
f
vÅÅÅÅÅÅÅÅ
b
N
2

m
+
1
F
=
2

ÅÅÅÅÅÅÅÅÅÅÅÅp
B
tan
-
1
J
Âf
vÅÅÅÅÅÅÅÅ
b
N
+
tan
-
1
J
f
vÅÅÅÅÅÅÅÅ
b
NF
Looking up the math handbook (do the trig if you like) gives tan
-
1

z
1
tan
-
1

z
2
=
tan
-
1
@H
z
1
z
2
LêH
1
¡
z
1

z
2
LD
:
F
H
v
,
f
,
z
L
º
2

ÅÅÅÅÅÅÅÅÅÅÅÅp
tan
-
1
ikjjjj
Âf
v
ê
b
+
f
v
ê
b
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
1
-
H
Âf
v
ê
b
L

H
f
v
ê
b
Ly{zzzz
=
2

ÅÅÅÅÅÅÅÅÅÅÅÅp
tan
-
1
ikjjj
2
H
v
ê
b
L

cos
fÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
1
-v
2
ê
b
2
y{zzz
Exactly as you should have found in 2.13. Note the shorter route to summing the series, those of you who'reinterested.
2

Problem 3.11
(a)The standard way to show orthogonality is to integrate the differential equation, in this case 3.77:0
=
2
J
n
H
x
L
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
x
2
+
1
ÅÅÅÅÅ
x

J
n
H
x
L
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
x
+
ikjjjj
1
-n
2
ÅÅÅÅÅÅÅÅÅ
x
2
y{zzzz

J
n
H
x
L
=
1
ÅÅÅÅÅ
x

ÅÅÅÅÅÅÅÅÅ
x

ikjj
x
ÅÅÅÅÅÅÅÅÅ
x

J
n
H
x
Ly{zz
+
ikjjjj
1
-n
2
ÅÅÅÅÅÅÅÅÅ
x
2
y{zzzz

J
n
H
x
L
(1)0
=
1
ÅÅÅÅÅÅ r
ÅÅÅÅÅÅÅÅÅÅ
r
ikjjj
r
ÅÅÅÅÅÅÅÅÅÅ
r
J
n
H
r
Ly{zzz
+
ikjjjj
2
-n
2
ÅÅÅÅÅÅÅÅÅ r
2
y{zzzz

J
n
H
r
L
Act on both sides with the integral operator
Ÿ
0
a

rr
J
n
H
r
L
and integrate stuff by parts:0
=
‡
0
a

r
ÅÅÅÅÅÅÅÅÅÅ
r
ikjjj
r
ÅÅÅÅÅÅÅÅÅÅ
r
J
n
H
r
Ly{zzz

J
n
H
r
L
+
‡
0
a

r
ikjjjj
r
2
-n
2
ÅÅÅÅÅÅÅÅÅ r
y{zzzz

J
n
H
r
L

J
n
H
r
Ly{zzzz
=
ÄÇÅÅÅÅÅÅÅÅ
r
J
n
H
r
L

ÅÅÅÅÅÅÅÅÅÅ
r
J
n
H
r
LÉÖÑÑÑÑÑÑÑÑ
0
a
-
‡
0
a

rr
J
n
H
r
L
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
r
J
n
H
r
L
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
r+
‡
0
a

r
ikjjjj
r
2
-n
2
ÅÅÅÅÅÅÅÅÅ r
y{zzzz

J
n
H
r
L

J
n
H
r
Ly{zzzz
We're given that the first term vanishes at the lower limit
r=
0 (is it just me or is this trivial, because
r=
0 at
r=
0??). The other condition says(2)
ÅÅÅÅÅÅÅÅÅÅ
r
ln
@
J
n
H
r
LDƒƒƒ§ƒƒƒ
r=
a
=
1
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
J
n
H
r
L

J
n
H
r
L
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
r
ƒƒƒ§ƒƒƒ
r=
a
=-lÅÅÅÅÅÅ
a
ïr
J
n
H
r
L
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
r
ƒƒƒ§ƒƒƒ
r=
a
=-l
J
n
H
k a
L
Incidentally we see from this that
is restricted to values such that (2) is satisfied, i.e.
k a
ª
y
n
n
such that
a

J
n£
H
y
n
n
L
+l
J
n
H
y
n
n
L
=
0. We can arbitrarily start numbering eigenvalues
n
=
1,2,….0
=-l
J
n
H
a
L

J
n
H
r
L
-
‡
0
a

rr
J
n
H
r
L
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
r
J
n
H
r
L
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
r+
‡
0
a

r
ikjjjj
r
2
-n
2
ÅÅÅÅÅÅÅÅÅ r
y{zzzz

J
n
H
r
L

J
n
H
r
Ly{zzzz
0
=-l
J
n
H
k a
L

J
n
H
r
L
-
‡
0
a

rr
J
n
H
r
L
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
r
J
n
H
r
L
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
r+
‡
0
a

r
ikjjjj
r
2
-n
2
ÅÅÅÅÅÅÅÅÅ r
y{zzzz

J
n
H
r
L

J
n
H
r
Ly{zzzz
In the last step I've just renamed
¨
. Subtracting the second line from the first gives what we want:0
=
‡
0
a

rr
I
2
-
2
M

J
n
H
r
L

J
n
H
r
L
=
I
2
-
2
M

‡
0
a

rr
J
n
H
r
L

J
n
H
r
L
since it means that unless
2
=
2
(in which case the right-hand-side is trivially 0) the integral must vanish.(b)Now normalization. This time act on (1) with
Ÿ
0
a

rr
2
J
n
H
r
Lê
r
and use
f
f
ÅÅÅÅÅÅÅÅÅ
r
=
1
ÅÅÅÅÅ
2

H
f
2
L
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
r
:
3
Search History:
Searching...
Result 00 of 00
00 results for result for
• p.
• Notes